Outcome of Locally Assembled Continous Positive Airway Pressure Device in Neonates with Respiratory Distress in Low Resource Setting (Nepal Medical College Journal, 2021)
Respiratory distress is the most frequent cause of neonatal admission in neonatal intensive care unit (NICU). Continuous Positive Airway Pressure (CPAP) is an effective mode of treatment in newborn with respiratory distress. CPAP is the application of positive pressure to the airways of spontaneously breathing patient throughout the respiratory cycle. Low cost CPAP can be locally assembled and used in neonates with respiratory distress to reduce the mortality. This is a cross sectional descriptive study conducted in NICU of Nepal Medical College Teaching Hospital from the period of June 2021 to September 2021 to assess the outcome of locally assembled CPAP. A total of 96 newborns with respiratory distress were included in the study. Severity of respiratory distress was assessed by Downes score. Downes score before and after CPAP were recorded. Newborn with Downes score of ≥4 was started with locally assembled CPAP. Outcome was taken as improvement when the respiratory distress was decreased with Downes score